2021
DOI: 10.3390/nu13072446
|View full text |Cite
|
Sign up to set email alerts
|

Administration with Quinoa Protein Reduces the Blood Pressure in Spontaneously Hypertensive Rats and Modifies the Fecal Microbiota

Abstract: Despite the well-established role of quinoa protein as the source of antihypertensive peptides through in vitro enzymolysis, there is little evidence supporting the in vivo antihypertensive effect of intact quinoa protein. In this study, in vivo study on spontaneously hypertensive rats (SHRs) was conducted by administering quinoa protein for five weeks. Gastrointestinal content identification indicated that many promising precursors of bioactive peptides were released from quinoa protein under gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
4
18
0
Order By: Relevance
“…Fermented soy proteins (200 mg/kg body weight) reduced systolic blood pressure (−19 mmHg) in spontaneously hypertensive rats during six-week feedings [145]. In a related work, 100 mg/kg bodyweight of the fermented soy proteins reduced both blood pressure (systolic (−27.1 mmHg), diastolic (−38.6 mmHg)), inhibited by 40% serum ACE activity, and increased the microbial richness and evenness relation to control SHRs [120]. At the phylum level, for example, Firmicutes represented 82% of all identified species in the fecal samples of control SHRs compared to 8% of Bacteroidetes.…”
Section: Mechanisms Via the Angiotensin Systemmentioning
confidence: 87%
“…Fermented soy proteins (200 mg/kg body weight) reduced systolic blood pressure (−19 mmHg) in spontaneously hypertensive rats during six-week feedings [145]. In a related work, 100 mg/kg bodyweight of the fermented soy proteins reduced both blood pressure (systolic (−27.1 mmHg), diastolic (−38.6 mmHg)), inhibited by 40% serum ACE activity, and increased the microbial richness and evenness relation to control SHRs [120]. At the phylum level, for example, Firmicutes represented 82% of all identified species in the fecal samples of control SHRs compared to 8% of Bacteroidetes.…”
Section: Mechanisms Via the Angiotensin Systemmentioning
confidence: 87%
“…Curcumin also restored BP by altering the composition of gut microbial community and improving gut pathology and integrity in SHRs 177 . Quinoa protein intervention decreased BP significantly and changed the microbial community structure in SHRs compared with nonhypertension rats 178 . A growing body of evidence has indicated that berberine and its derivatives could reduce BP in patients with hypertension, and its mechanism may be attributed to inhibition of renin‐angiotensin system activity, 179 decreased levels of aldosterone, 179,180 reduced arterial stiffness, 181 and improved endothelial function 180 in rats.…”
Section: Treatment Of Hypertension Based On Gut Microbesmentioning
confidence: 92%
“…177 Quinoa protein intervention decreased BP significantly and changed the microbial community structure in SHRs compared with nonhypertension rats. 178 A growing body of evidence has indicated that berberine and its derivatives could reduce BP in patients with hypertension, and its mechanism may be attributed to inhibition of renin-angiotensin system activity, 179 decreased levels of aldosterone, 179,180 reduced arterial stiffness, 181 and improved endothelial function 180 Previous studies have provided enough evidence that gut microbes can regulate BP. However, there is still a long way to go before gut microbes can be applied to improve hypertension.…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…During the five weeks of intake of quinoa protein, the blood pressure (BP) was significantly decreased, while the alpha diversity was increased, and the microbial structure was changed. Subsequent analysis revealed that the abundances of Turicibacter and Allobaculum genera were negatively correlated with BP [67].…”
Section: Hypertensionmentioning
confidence: 99%